Emotion and Proactivity at Work : Prospects and Dialogues - Peng, Kelly Z. (Book collections on Project MUSE., 2021)
In this pioneering work, expert scholars offer new thinking on proactivity by examining how emotion can drive employees' proactivity in the workplace and how, in turn, that proactivity can shape one's emotional experiences.